ANALISIS PERBEDAAN JUMLAH TOTAL BELANJA ANTARA LAKI-LAKI DAN PEREMPUAN MENGGUNAKAN UJI ANOVA - Raihan Nuraditya Pratama; Angga wicaksana, Ayub Trisna Mukti, Farell Muhammad Dava, Rafli Nurfirmansyah, Rivaldi Rasqi Alzahab (Jurnal Ekonomi dan Bisnis, 2024)
In the era of globalization and rapid economic development, people's consumption patterns are experiencing significant changes. Factors such as gender and age often influence an individual's shopping habits. In hypothesis testing, it is necessary to carry out prerequisite tests. Prerequisite tests are a series of tests carried out before carrying out the main statistical analysis to ensure that the data meets the assumptions needed for the analysis to be valid and accurate. The method used to carry out the analysis of differences in total expenditure is the ANOVA method. It can be said that the significance level of total spending is not influenced by gender. It can be said that age does not have a significant effect on the total amount of spending.